Heteroduplex formation by recA protein: polarity of strand exchanges. - West, S C (1981)
Purified recA protein promotes strand exchanges between linear duplex DNA and homologous circular single-stranded phage phi X174 DNA that carries a short hybridized fragment [West, S. C., Cassuto, E. & Howard-Flanders, P. (1981) Proc. Natl. Acad. Sci. USA 78, 2100-2104]. In this paper we investigate the mechanism of this strand exchange reaction. We show that recA protein initiates strand exchanges by pairing the free end of the duplex fragment with the single-stranded DNA. In addition, we find that strand exchanges are polar, stable heteroduplex molecules being formed by the directional transfer transfer of the (-) strands starting at 3' termini.